Metode Talfik Di Sudan Sebagai Wujud Perkembangan Hukum Keluarga Islam - Elkhairati, Elkhairati (Berasan: Journal of Islamic Civil Law, 2023)
The reform of Islamic family law should involve a process of consultation, dialogue, and participation involving scholars, Islamic jurists, religious leaders, and the Muslim community at large. The aim is to strike a balance between maintaining the tenets of the Islamic religion and meeting the needs and aspirations of modern Muslim societies. In this study, the highlight is the renewal of Islamic family law in Sudan. The method used in this study is a qualitative approach and is a type of library research. Library research method, also known as literature research or literature research, is a research approach that involves the use of library and library resources as the main source of information. This method relies on the analysis of previously published relevant literature, such as books, journals, articles, reports, and other documents. The birth of legal products in Sudan, full of dynamics and colors. Starting from the formalistic Islamization of law carried out by Numeiri, until the end, Sudan is now divided into two states. In the context of Islamic family law in Sudan and Indonesia, there are prominent and almost identical differences. A very prominent difference is seen in terms of legislation. In Sudan, all forms of statutory decisions are given full rights to Judges. In Sudan, judges are acquitted of their legal rulings. Sudan's talfic method of formalizing the law became commonplace and not foreign or taboo.